Natural gas consumption and economic growth: Are we ready to natural gas price liberalization in Iran? - Heidari, Hassan; Katircioglu, Salih Turan; Saeidpour, Lesyan (Elsevier Sci Ltd, 2013)
This paper examines the relationship between natural gas consumption and economic growth in Iran within a multivariate production model. We also investigate the effects of natural gas price on its consumption and economic growth using a demand side model. The paper employs bounds test approach to level relationship over the period of 1972-007. We find evidence of bidirectional positive relationship between natural gas consumption and economic growth in short-run and long-run, based on the production model. The findings also suggest that real GDP growth and natural gas have positive and negative impacts on gross fixed capital formation, respectively. Employment, however, was found to have negative but insignificant impact on gross fixed capital formation. Moreover, the estimation results of demand side model suggest that natural gas price has negative and significant impact on natural gas consumption only in the long-run, though there is insignificant impact on economic growth. These results imply that the Iranian government's decision for natural gas price liberalization has the adverse effects on economic growth and policy makers should be cautious in doing this policy.. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Economic growth; Natural gas consumption; Iran